PENGARUH KUALITAS PELAYANAN DAN BAGI HASIL TERHADAP KEPUASAN NASABAH: (Studi Pada Bank Syariah Mandiri Kantor Cabang Majalengka) - Endah Prihartini (Jurnal Co Management, 2019)
This study aims to find out how the influence of service quality and profit sharing both partially and simultaneously on the satification of customer of Mandiri Syariah Bank Majalengka branch office. The population in this study were customers of Mandiri Syariah Bank Majalengka branch office, which was taken as respondents, amounting to 100 people. The research method used is a survey method with a descriptive verification approach. The analytical tool used in this study is the classical assumption, multiple regression analysis, coefficient of determination analysis, and hypothesis testing for partial test using t test and simultaneous test using F test. The results of the study indicate that both partially and simultaneously service quality and profit sharing have a significant effect on customer satisfaction. Meaning the higer the quality of service and the better the profit sharing, customer satisfaction will increase.